Hormonal, antioxidant, and body composition differences in national level male athletes: a comparative study of aerobic and anaerobic training - Jaradat, M. B.; Maghayreh, E.; Husain, W.; Trabelsi, K.; Amawi, A.; Jahrami, H.; Ghazzawi, H. A. (Frontiers in Sports and Active Living, 2025)
Background: Competitive athletes exhibit distinct physiological adaptations depending on their sport type and training techniques. These variations influence body composition, hunger-regulating hormones, and antioxidant defense mechanisms, which collectively impact performance, recovery, and progression. This study aimed to compare body composition, serum levels of ghrelin, leptin, and glutathione (GSH), and their interrelationships in national level male athletes engaged in aerobic and anaerobic sports.